2010
DOI: 10.1210/me.2010-0117
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Farnesoid X Receptor Provides Protection against Acetaminophen-Induced Hepatic Toxicity

Abstract: The nuclear receptor, farnesoid X receptor (FXR, NR1H4), is known to regulate cholesterol, bile acid, lipoprotein, and glucose metabolism. In the current study, we provide evidence to support a role for FXR in hepatoprotection from acetaminophen (APAP)-induced toxicity. Pharmacological activation of FXR induces the expression of several genes involved in phase II and phase III xenobiotic metabolism in wild-type, but not Fxr(-/-) mice. We used chromatin immunoprecipitation-based genome-wide response element ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 51 publications
2
67
0
Order By: Relevance
“…Recent studies have indicated the protective role of FXR signaling in chemical-induced liver injury. [29][30][31] Because FGF15/19 signaling is up-regulated by FXR activation, it probably participates in the protection of hepatic function. The present study raises the possibility of application of the FGF19 signaling pathway to liver disorders, such as non-alcoholic fatty liver disease with insulin resistance, since Fxr-null mice seem to be models of the metabolic syndrome with hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated the protective role of FXR signaling in chemical-induced liver injury. [29][30][31] Because FGF15/19 signaling is up-regulated by FXR activation, it probably participates in the protection of hepatic function. The present study raises the possibility of application of the FGF19 signaling pathway to liver disorders, such as non-alcoholic fatty liver disease with insulin resistance, since Fxr-null mice seem to be models of the metabolic syndrome with hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…FXR has been shown to have relevance in the attenuation of clinically important conditions such as gallstone disease ( 11,12 ), cholestasis ( 13 ), and fatty liver disease ( 14 ). Most of these hepatoprotective functions of FXR can be attributed to the induction of genes involved in bile acid detoxifi cation and xenobiotic metabolism, including phase I oxidation enzyme CYP3A4 ( 15 ) and a number of phase II conjugation enzymes ( 16 ) and phase III effl ux transporters ( 10 ).…”
mentioning
confidence: 99%
“…Upon bile acid binding, FXR positively regulates a series of genes responsible for maintaining normal liver physiology, thus protecting the hepatocyte from environmental insults (Huang et al, 2006;Lee et al, 2010a). In particular, CDCA is a major bile acid constituent that exerts a hepatoprotective effect by activating FXR.…”
Section: Noh Et Almentioning
confidence: 99%
“…FXR functions as a ligand-mediated transcription factor by binding to specific DNA motifs in the promoter regions of target genes, and it regulates the expression of various genes involved in bile acid, lipid, and glucose metabolism (Wang et al, 1999). FXR plays a role in the induction of genes encoding for proteins involved in xenobiotic metabolism and detoxification (Urquhart et al, 2007;Lee et al, 2010a). Bile acids are synthesized from cholesterol by a series of enzymatic reactions in hepatocytes and work as a digestive surfactant, promoting lipid absorption (Lefebvre et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation